Examining the Heterogeneity of Exercise Response Among Sedentary Older Adults: A Descriptive Analysis - Grace L. Kulik; Melissa P. Wilson; Catherine M. Jankowski; Lindsay T. Fourman; Kristine M. Erlandson (Journal of Aging Research)
Trial Registration: ClinicalTrials.gov identifier: NCT02404792